Navigating Virtual Reality Worlds with the Leap Motion Controller - Rui Miguel de Paiva Batista (2016)
Real state tours is a process where a potential buyer visits a house to know more details about it. This is an inefficient process at several levels. The user needs to travel physically to the house which brings monetary costs and it is a time consuming activity. To mitigate these factors the market is starting to have virtual real state tours. These have several benefits and the main advantage is the user only having to dislocate to a access point like a personal computer. Virtual tours also have its disadvantages. The houses built in virtual environments, although detailed, can not give the potential buyer the feeling of presence. Normally the buyer can only look at pictures of rooms or see the virtual house in a broad perspective like a blueprint. Virtual reality can bring to the real state market the feeling of presence. Using devices like the Oculus Rift, users can be placed in a virtual reality property with a first person perspective. This brings some new challenges like navigation. The dissertation Navigating Virtual Reality Worlds with the Leap Motion Controller main goal is to find and evaluate several navigation methods to control a virtual character inside a virtual simulator. Recent devices as the Leap Motion will be compared with more traditional devices, like the gamepad. To accomplish the goals set in this dissertation, tools like a game engine (Unity3D or Unreal Engine) will be utilized. Leap Motion is a recent device to interact with virtual worlds. It can detect in real time the position direction and arch from user's hands. When combined with Oculus Rift, a device that through stereoscopic vision offers the user a first person perspective which allows the user to interact with the virtual world with a greater level of immersion. With the main goal set, some frequent problems with immersive simulators will be considered (for example, the user's fatigue). To help create the virtual world a game engine will be utilized. A survey of the main game engines will be made and one of them will be chosen to create the final application. The main use case scenario will be a real estate virtual tour. A user that can not travel to an apartment can, through the application, make a virtual tour to it anywhere in the world. With the first perspective feature given by the Oculus Rift, the user can have a immerse tour and have a realistic view of the apartment. However, it will be necessary to navigate through the property. Using a device like the Leap Motion, the user can interact with the world without losing the immersion factor. The main use case scenario has some requirements that must be taken into account. Has the target audience is every one over eighteen years old, the learning curve of the techniques must be low and the devices must be simple to handle. Also, effects related with the use of the Oculus Rift will be taken into consideration and evaluated, like motion sickness and fatigue. To evaluate the several techniques some tests will be made to the users, like the Simulation Sickness Questionnaire(SSQ). These act like comparison tools to test virtual reality simulators.